Hem-o-lok Clips Migration: An Easily Neglected Complication after Laparoscopic Biliary Surgery - Jun-wen Qu; Gui-yang Wang; Zhi-qing Yuan; Ke-wei Li (Case Reports in Surgery)
Clip migration into the common bile duct (CBD) is a rare but well-established phenomenon of laparoscopic biliary surgery. The mechanism and exact incidence of clip migration are both poorly understood. Clip migration into the common bile duct can cause recurrent cholangitis and serve as a nidus for stone formation. We present a case, a 54-year-old woman, of clip-induced cholangitis resulting from surgical clip migration 12 months after laparoscopic cholecystectomy and laparoscopic common bile duct exploration (LC+LCBDE) with primary closure.